2000
DOI: 10.1074/jbc.m000655200
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Homeodomain Transcription Factor IDX1/IPF1 Expressed in Developing Brain Regulates Somatostatin Gene Transcription in Embryonic Neural Cells

Abstract: Hox-like homeodomain proteins play a critical role during embryonic development by regulating the transcription of genes that are important for the generation of specific organs or cell types. The homeodomain transcription factor IDX1/IPF1, the expression of which was thought until recently to be restricted to the pancreas and foregut, is required for pancreas development and for the expression of genes controlling glucose homeostasis. We report that IDX1/IPF1 is also expressed in embryonic rat brain at a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…6B). Previously, we described that IDX1, a different homeodomain protein present in neural cells binds the SMS-UE-B element (35). Most interestingly, we found that the addition of two different anti-IDX1 antisera to the binding reaction resulted in the disappearance of the same band that disappears with the anti-Alx3 antiserum, suggesting that the protein complex bound to SMS-UE-B may contain both homeoproteins (Fig.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…6B). Previously, we described that IDX1, a different homeodomain protein present in neural cells binds the SMS-UE-B element (35). Most interestingly, we found that the addition of two different anti-IDX1 antisera to the binding reaction resulted in the disappearance of the same band that disappears with the anti-Alx3 antiserum, suggesting that the protein complex bound to SMS-UE-B may contain both homeoproteins (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…For comparison, we also used nuclear extracts of pancreatic isletderived somatostatin producing RIN-1027-B2 cells. We have previously shown that nuclear proteins from both RC2.E10 and RIN-1027-B2 cells bind to somatostatin TAAT-containing elements forming several sequence-specific protein-DNA complexes (18,33,35). Expression of Alx3 in RC2.E10 and RIN-1027-B2 cells was confirmed by Western blot (Fig 6A).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations